Development of mass business in Kazakhstan - Daribayeva, A.K.; Kurmankulova, N.Zh.; Karbetova, Sh.R. (BUKETOV BUSINESS REVIEW, 2018)
The article discusses the development of mass entrepreneurship in Kazakhstan. The authors pay special attention to the study of the current state of entrepreneurship in Almaty, as it is the largest financial, innovative, tourist and cultural center of the country and occupies a leading position among other regions of Kazakhstan in terms of gross regional product and in terms of output of real products of small and mediumsized businesses.The article analyzes the implementation of the current Program for the Development of Productive Employment and Mass Entrepreneurship in Almaty, the volume of microcrediting has been expanded, the article analyzes the dynamics of the number of microcredit organizations in the Republic of Kazakhstan in 2012–2016, the analysis of the basic indicators of activity of subjects of SMEs for 2012–2016, a share of small and medium business in the country’s GDP is presented. Based on the analysis, an evaluation of the implementation of the Program is given and proposals for the further development of mass entrepreneurship are developed. The conducted researches also show that one of the priority directions in the activity of regional authorities is the following activities: simplification of procedures for registration of selfemployed individual entrepreneurs and introduction of their free registration, as well as tax reduction for newly registered entrepreneurs.